A Corporate Social Responsibility Analysis of Payday Lending. (26th September 2018) - Schwartz, Mark S.; Robinson, Chris
Abstract: In this article, we use a corporate social responsibility (CSR) framework to analyze the payday loan industry by critically examining its practices from an economic, legal, and ethical perspective. Payday loans are essentially a very high cost, unsecured, short‐term personal loan. Given the inherent nature of the product being offered, the industry appears on the face of it to be in a position to potentially exploit vulnerable consumers in pursuit of profits. With this concern in mind, our analysis investigates the following three issues: Can the payday loan industry currently be considered to be acting in a socially responsible manner? If the industry cannot be considered to be socially responsible, should it be further regulated? If the industry should be further regulated, how should it be regulated? To address these issues, we first provide a brief historical overview of payday loans. Second, we describe the important characteristics of payday loans and how the industry operates. Third, we draw on various sources of evidence to demonstrate that the payday loan industry, while fulfilling its basic economic obligations, falls outside of both the legal and ethical domains of the Three Domain Model of CSR. Based on our analysis, our conclusion is that the payday loan industry requires additional government legal regulation, particularly with respect to allowable fees, and we conclude that there is a strong ethical case for banning payday loans altogether.